Agritourism in Poland – self governments’ views versus reality - Bednarek-Szczepańska, Maria (Discussion Papers, 2011)
The idea of agritourism development has been very popular since the beginning of political-economic transformation in Poland. Agritourism is perceived in different circles (self-governments, scientists, media) as an opportunity of development of many rural regions. The self-governments’ views on agritourism and on its potential significance for rural areas, as contained in the selected regional and local strategies, programmes and plans, are reviewed in the paper. Against this background, the actual situation in agritourism in Poland is presented. Analysis of the development documents on the regional scale confirms an assumption that regional authorities are very interested in agritourism development. Unfortunately, the formulations related to agritourism suggest (are indicative of) superficial knowledge of that matter possessed by the authors of the documents, lack of in-depth analysis of internal and external conditions, including competition with other regions. The authors in most cases copy the “fashionable” models of rural development. The review of local documents reveals a great discrepancy between local self governments’ views on agritourism and the reality. Despite the fact that there were no agritourism facilities in several investigated communes and that the communes’ attractiveness for this kind of tourism was rather low, the popularity of the agritourism concept was very high among local self-governments. The concept of agritourism as a development opportunity for Polish rural areas has a lot in common with a myth – a kind of illusion existing not only in self-governmental, but also in non-governmental and academic circles.